Conflict of Government Policy in Tolitoli Regency, Central Sulawesi Province - Pasinringi, Andi; Darwis, Darwis; Samad, Muhammad Ahsan (International Journal Papier Public Review, 2020)
This study aims to determine how the policy conflict between the Regent and Deputy Regent of Tolitoli Regency, Central Sulawesi Province. The basis of research is carried out with a qualitative approach, while the type of research is exploratory. This research was conducted in Tolitoli Regency with the basis of the problem being the conflict of Regent Moh. Saleh Bantilan with Deputy Regent ABD Rahman Hi. Buddin. In this study, it was found that the root causes of conflict were conflicts of political interest in policies and authority to organize the Bureaucratic Structure in the levels of the Tolitoli Regency Regional Government which occurred in the two periods 2010-2015 and 2015-2020. The data collection techniques used are; first, literature study, by searching literature and documents related to the scope of research. second, in-depth interviews with research informants who have been determined purposively. The results of the study revealed that there was a political policy conflict between the Regent, Moh. Saleh Bantilan with his representatives for two periods, in which Moh Saleh Bantilan monopolized the authority in carrying out his duties and functions as Regent whose authority is regulated in Regional Government Law Number 23 of 2014. And this Law does not explicitly and clearly regulate the powers and the obligations of regional heads and deputy regional heads. Thus, the Political Policy conflict occurred, as a result of the transactional political construction agreed upon by both parties when they were candidates for regent and deputy regent, and after being elected as Regent / Deputy Regent, there was a split between the Regent and his deputy. Regional Government bureaucracy does not work professionally.